(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This is an article on the theory of scientific theory, its role in science and its practical significance. A scientific theory is a set of assumptions that serve to explain and predict phenomena. In psychology, these theories provide a fundamental theoretical basis for understanding the complexities of human behavior and consciousness.